COVID-19 pandemic: Restrictions and functionality in the knees of physiotherapy students, preliminary study: Funcionality in knees of students - Machado Viegas Trindade , Andrei; Pinheiro Rezende, Leonardo; Rodolfo Borges Parreira, Rodolfo; Barbosa Cordeiro , Lorraine; Rocha da Silva Araújo , Helder; Rodrigues Torres , Marcelo; Santos Oliveira , Claudia (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: The COVID-19 pandemic declared by the WHO in 2020 led to restrictive measures that exerted an impact on physical activity, which can affect musculoskeletal health. Objective: The aim of the present study was to analyze the impact of the pandemic on knee pain and functioning among university students influenced by social isolation measures. Methods: An observational, cross-sectional study was conducted at the Evangelical University of Goiás (UniEVANGELICA) with 52 physiotherapy students. Data were collected with the aid of an online questionnaire addressing lifestyle habits, physical activity, knee pain, and functioning using the Lysholm knee score. Data analysis was performed with SPSS 21, using appropriate statistical tests. Results: The chi-square test revealed no significant association between COVID-19 and knee pain, but an apparent relationship was found between physical activity and pain. No significant association was found between COVID-19 and worse walking function, although a tendency was suggested. Discussion: Despite the apparent association between physical activity and pain, the lack of statistical significance indicates the need for more detailed analyses. The present results diverge from those of global studies, underscoring the complexity of the relationship between the pandemic and musculoskeletal health. Limitations of the study include the sample size and self-reporting. Conclusion: This study provides insights into the relationships between COVID-19, knee pain, physical activity, and walking function in university students. Although no significant association was found in some analyzes performed in this study, caution should be exercised when interpreting the results. Further research considering additional variables is recommended to gain a robust understanding of these relationships.